О древнерусских источниках легендарной части летописей Великого Княжества Литовского - Морозова, Н. А. (Kalbotyra, 1992)
The article is devoted to the analysis of the structure of legendary part of Lithuanian Chronicles and the Tale of Bygone Years. The comparison of the texts of the Lithuanian and Old Russian Chronicles shows that Lithuanian chronicle is standing in close relation to the Old Russian one. In general we can say that Old Russian Chronicle (The Tale of Bygone Years) was the structural and literary model to the legendary part of the Lithuanian Chronicles.